Essentials for a Successful Employment Injury Insurance System A Practical Guide on Policy, Institutional Governance, Legislation, Administration and Sustainable Finance. (International Labour Organisation (ILO), 2021)
Essentials for a successful employment injury insurance system is part of the training material produced by the ILO in response to an identified need to build national capacity for effective governance and management of an employment injury social security (EISS) system.